2005
DOI: 10.1161/01.str.0000181754.38408.4c
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Inflammatory and Hemostatic Variables With the Risk of Recurrent Stroke

Abstract: Background and Purpose-Several prospective studies have shown significant associations between plasma fibrinogen, viscosity, C-reactive protein (CRP), fibrin D-dimer, or tissue plasminogen activator (tPA) antigen and the risk of primary cardiovascular events. Little has been published on the associations of these variables with recurrent stroke. We studied such associations in a nested case-control study derived from the Perindopril Protection Against Recurrent Stroke Study (PROGRESS). Methods-Nested case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 44 publications
8
90
0
4
Order By: Relevance
“…Fibrinogen is a thrombotic risk factor which also acts as an acute phase protein. Elevated levels of fibrinogen have been reported after stroke [4] and have been associated with increased risk of recurrent stroke [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen is a thrombotic risk factor which also acts as an acute phase protein. Elevated levels of fibrinogen have been reported after stroke [4] and have been associated with increased risk of recurrent stroke [9].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In metaanalysis of studies of long term follow up, Preindropil Protection Against Recurrent Stroke (PROGRESS) clinical trial and "Benzfibrate Infarction Prevention (BIP) Study" the figures for recurrent event was 1.7, 1.34 and more than two fold increased risk in highest versus lowest tertile group respectively. [10][11][12] In addition, raised CRP levels may reflect the clinical course of the condition extent of brain infarction and an adverse prognosis. [13][14][15][16] In all these studies focus was on mortality at one month and thereafter.…”
mentioning
confidence: 99%
“…Woodward et al (27) , in their study covering 591 stroke patients (83 hemorrhagic, 472 ischemic), has shown that fibrinogen level was significantly higher in patients with ischemic stroke. In our study, fibrinogen levels of 65 of 100 patients were high (>3.5 g/L) and of these patients 24.6% had TIA, 43.1% had ischemic stroke, and 32.3% had hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 95%